The Impact of the Application of the Balanced Scorecard in Improving Performance: An Empirical Study on the Commercial Banks in Jeddah - Al-Rashed, Taghreed; Damanhouri, Amal (The Arab Journal of Administration, 2018)
The implementation of the Balanced Scorecard to improve performance in commercial banks in the city of Jeddah, Saudi Arabia is the focus of this study. Specifically, this study investigates the effect of the financial perspective, the customer perspective, the internal process perspective, and the learning and growth perspective of Balanced Scorecard on improving the performance of these banks. A stratified random sample was adopted to determine the sample size in the branches of commercial banks under study. The sample of the study was 206 managers and deputy managers of branches of banks. A descriptive analytical method was applied using a questionnaire. Data were analyzed in SPSS using the appropriate descriptive and analytical statistical techniques. The results of indicated that rapprochement of averages of the application of all the dimensions of the Balanced Scorecard (high level) except the learning and growth (the average level). It has also become apparent through the study that there is a positive impact between all the dimensions of the Balanced Scorecard and improved performance. However, these dimensions can influence improved performance in varying proportions, and the level of impact can be arranged in the following order: the internal process, the customer perspective, the learning and growth perspective, finally the financial perspective. A number of recommendations have been reached which could aid in improved performance in commercial banks in the city of Jeddah; in particular develop a model of the Balanced Scorecard dimensions affecting improved performance.